Green’s Equivalence Classes in Full Transformation Semigroups: A Height-based Approach - Idayat, Usamot Foluke; Risqot, Ibrahim Garba; Naimat, Bakare Gatta; Dauda, Adeshola Adediran; Olaniyi, Aliu Tajudeen (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
Green’s relations constitute five distinct equivalence classes that serve to define the elements of a semigroup. In this work, the equivalence classes within the Full Transformation Semigroup (Tκ) were systematically enumerated according to their respective heights, and the findings derived were subsequently generalized through the application of a combinatorial assertion and their graphical representations included to substantiate the theoretical results.